Strategiese bemarkingsbestuur by enkele leweransiers aan die landbou in die Republiek van Suid-Afrika - J. J. Van Zyl (South African Journal of Business Management, 1986)
Strategic marketing management of some suppliers to the Agricultural sector in the Republic of South Africa The Republic of South Africa is at present in a state of change within the economical, political, social, institutional, physical and international environments. Change in these fields is still in an early phase and rapid changes can be expected in future. From a management point of view, these changes are a fact and must be considered and taken into account in the decision-making process. Modern enterprise in the free-market system functions within the framework of the changing environment and the ability to grow and develop are dependent on the ability of the individual firm to adapt to these changes. The aim of the research was to determine how marketing management of some suppliers of capital equipment to the agricultural sector apply strategic marketing principles and practices, to enable their firms to adapt to constant external changes. Apart from a theoretical background some empirical research was undertaken to determine the composition of the management and marketing strategies. The emphasis is, however, on the formulation of the marketing strategy and the implementation of the marketing strategy.
Keywords: 650